Avaliação da influência da enzima polifenoloxidase na produção de etanol - Sousa, Gabriel Torres de (Universidade Federal de São Carlos, 2024)
The production of ethanol from sugarcane plays a crucial economic, social, and environmental role in Brazil, generating income and development in a country that is a global benchmark in biofuel and renewable energy production. Among the various stages and characteristics of ethanol production, the occurrence of enzymatic browning reaction can be observed shortly after sugarcane milling, catalyzed by the naturally present polyphenoloxidase (PFO) enzyme in the plant. This enzyme comes into contact with its substrates and oxygen immediately after juice extraction, triggering a series of chemical reactions that produce, among other compounds, phenolic and polymeric substances that generate sludge and impart a dark color to the sugarcane must. In this context, the motivation for this study was to evaluate the influence of the enzymatic browning reaction and its products on ethanol production through the fermentation of sugarcane juice under different concentrations of Saccharomyces cerevisiae yeast and thermal inactivation of the PFO enzyme before the milling stage. The results obtained showed that the thermal inactivation of the enzyme led to a lower generation of sludge in the sugarcane must, a positive aspect for alcohol production. Enzymatic inactivation did not result in increased ethanol production in the study, even at different yeast concentrations. The average distillate yield from treatments without thermal treatment (STT) with 0.5 g/L of yeast, STT with 1.0 g/L of yeast, and with thermal treatment (CTT) with 1.0 g/L of yeast showed no statistical difference by the Tukey test (p <0.05). However, the CTT sample with 0.5 g/L of yeast showed statistically lower distillate production than the others, indicating that the severe thermal treatment applied to the CTT samples at the beginning of the process may have eliminated a large majority of naturally occurring wild yeasts in the plant, reducing the volume of ethanol produced during fermentation. It is concluded that the thermal inactivation of PFO does not influence the volume of ethanol produced by the fermentation of sugarcane juice by Saccharomyces cerevisiae at yeast concentrations of 1.0 g/L.
Evaluation of the influence of polyphenoloxidase enzyme on ethanol production
Keywords: Fermentação; Polifenoloxidase; Escurecimento enzimático; Cana-de-açúcar; Ethanol; Fermentation; Polyphenol oxidase; Enzymatic browning; Sugarcane; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS